2020
DOI: 10.29252/johe.9.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Road Traffic Accidents and Associated Factors in Chuko Town, Southern Ethiopia, 2017

Abstract: Article InfoBackground: A road traffic accident is an incident on a way or street open to public traffic, resulting in one or more persons being killed or injured, and involving at least one moving vehicle. The purpose of this study was to present the prevalence and factors associated with road traffic accident in Chuko town , Southern Ethiopia Materials and Method: Community based cross sectional study was done in Chuko Town with a total sample size of 422 from March 27 to April 4, 2009 E.C Questionnaire cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
(16 reference statements)
0
6
2
Order By: Relevance
“…Implementation of strategies to combat RTAs includes road safety training courses for young people and adults aimed at raising awareness and changing the attitudes of their participants, influencing the intention to change behaviors toward more appropriate and less risk factors among drivers, and evaluations of different types of programs regarding road traffic, which specifically focused on resilience, risk detection, and decision-making that have proven to be the most useful (52). However, the result is somewhat lower than the study results reported in Mekelle Town (26.4%) (33), Chuko Town (23.5%) (32), and Ethiopia (21.9%) (15). The observed variation may be attributed to variations in the data sources, study participants, study settings, and sample size (15,32,33).…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Implementation of strategies to combat RTAs includes road safety training courses for young people and adults aimed at raising awareness and changing the attitudes of their participants, influencing the intention to change behaviors toward more appropriate and less risk factors among drivers, and evaluations of different types of programs regarding road traffic, which specifically focused on resilience, risk detection, and decision-making that have proven to be the most useful (52). However, the result is somewhat lower than the study results reported in Mekelle Town (26.4%) (33), Chuko Town (23.5%) (32), and Ethiopia (21.9%) (15). The observed variation may be attributed to variations in the data sources, study participants, study settings, and sample size (15,32,33).…”
Section: Discussionmentioning
confidence: 58%
“…Using the standard formula for a single population proportion, the sample size was calculated. By taking into account 33.4% of traffic accidents on the roads due to bad road conditions in Chuko Town, Ethiopia (32), at a 95% confidence interval (CI). where n = size of the sample; Zα/2 = 1.96 standard scores, with a 95% confidence interval; d = level margin of error to be tolerated (5%); and p = proportion of RTAs.…”
Section: Determining the Sample Size And Sampling Methodsmentioning
confidence: 99%
See 3 more Smart Citations